Persepsi Pengguna terhadap Implementasi Prinsip Desain Biophilic dalam Rancangan Bangunan Kos Keputih di Surabaya - Hakim, Muhammad Naufal; Rifti, Salsabila Melka; Samudera, Muhammad Daffa; Defiana, Ima (Architecture Department University of Merdeka Malang, 2024)
Biophilic design principles emphasize the relation between human, nature, and building to improve the quality of built environment. Nowadays, the availability of communal space as workplace in co-living building has become a common need. In Surabaya, Andy Rahman is one of the architect who expresses his concern about this phenomenon by designing co-living building with workplace, while prioritize local design and natural system. The objects of this study are three co-living building that are designed by Andy Rahman, located in Keputih, Surabaya. This study aims to describe how users experience and perceive the elements of biophilic design within the objects of study case. This research implements qualitative strategy to examine user’s perception of biophilic design principles in the design of each co-living building. Qualitative methods purports to describe the real life conditions of research subject. The data are collected by observation and interviews. The participants consist of university students that each have lived in the study case building for at least a year. The analysis is carried using the theory of biphilic design patterns and interior elements of biophilic design. The results show that there is an incremental changes among the object of the study regarding the quantity of perceived aspect. However, the results show that all three building designs are dominated by the sampe aspects. Moreover, the results indicates that the participants have different abilities in associating each design parameter